Perancangan Alat Pendingin Susu Sapi Menggunakan Solar Panel - Sulistiyanto, Sulistiyanto; Bahar, Syaiful; Hidaytullah, Aditya Arif (Jurnal Teknik Elektro dan Informatika, 2022)
Pondok Pesantren Nurul Jadid has or has a solar power plant (PLTS) where the plant is still unknown the angle of slope of current and power. By analyzing solar power plants using avometers to find out current and power while arc to find out the angle of tilt on the appearance of solar panels. In the retrieval of data on solar power plants by modifying the angle of tilt at the appearance from 0Âº to 45Âº. Where in analyzing solar panels to take current and power data released on photofoltaic is done repeatedly at a predetermined slope and clock. To measure the current and power released by the photofoltaic at the specified slope and clock, use the avometer and calculate the results of the analysis with a predefined formula (Pout = V. I).